Increased formation of neutrophil extracellular traps in patients with anti-N-methyl-d-aspartate receptor encephalitis - Qiao, Shan; Sun, Quan-ye; Zhou, Peng; Zhang, Shan-chao; Wang, Zhi-hao; Li, Hai-yun; Wang, Ai-hua; Liu, Xue-wu; Xin, Tao (Frontiers in Immunology, 2022)
Neutrophil extracellular traps (NETs) have been found to play an important role in several nervous system diseases. However, their role in anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis remains unclear. The purpose of this study was to examine the possible role of NETs in anti-NMDAR encephalitis. Eleven patients with anti-NMDAR encephalitis and ten healthy participants were enrolled. Plasma NETs levels were detected using an immunofluorescence assay and enzyme-linked immunosorbent assay. Additionally, we examined 10 plasma cytokines in patients with anti-NMDAR encephalitis and analyzed the correlation between citrullinated histone 3 levels and cytokine release. Peripheral blood neutrophils from patients with anti-NMDAR encephalitis were more susceptible to NET generation. When compared with controls, cases of anti-NMDAR encephalitis showed elevated levels of IL-1 α, IL-6, IL-8, IL-13, MCP-1, and TNF-α (p < 0.05). Moreover, IL-6, IL-8, and TNF-α levels were positively correlated with H3Cit levels. In conclusion, we provide evidence that NETs may play a role in anti-NMDAR encephalitis, providing clues for elucidation of the pathogenesis of this disease.